The Role of Ethnicity, Gender and Diversity of Director's Experience on Company Performance - Anita Ade Rahma; Titah Fadhilah Harahap; Desi Ilona; Febri Aldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aimed to analyze the influence of ethnicity, gender and board of director’s experience diversity on the company performance. The data used are secondary data from the financial statements and annual report from 2011 to 2017. Samples were taken randomly on all companies listed in Indonesia Stock Exchange as many as 266 companies. The results of this study prove that ethnicity and experience of the board of directors not significantly effect on company performance (ROS). However, the results of gender on board of directors showed negative and significant impact on company performance (ROS). Company age and audit quality have insignificant effect on company performance (ROS).